2016
DOI: 10.1152/physrev.00041.2015
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Development and Disease: Background, Mechanisms, and Therapeutic Approaches

Abstract: Advances in RNA-sequencing techniques have led to the discovery of thousands of non-coding transcripts with unknown function. There are several types of non-coding linear RNAs such as microRNAs (miRNA) and long non-coding RNAs (lncRNA), as well as circular RNAs (circRNA) consisting of a closed continuous loop. This review guides the reader through important aspects of non-coding RNA biology. This includes their biogenesis, mode of actions, physiological function, as well as their role in the disease context (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
1,165
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,492 publications
(1,173 citation statements)
references
References 311 publications
(316 reference statements)
6
1,165
0
2
Order By: Relevance
“…Long noncoding RNAs (lncRNAs) are non protein coding RNAs ranging from 200 nt to 100 kb in length [7]. The past decade has witnessed the discovery of diverse IncRNAs involved in physiological and pathological processes [8-12].…”
Section: Introductionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are non protein coding RNAs ranging from 200 nt to 100 kb in length [7]. The past decade has witnessed the discovery of diverse IncRNAs involved in physiological and pathological processes [8-12].…”
Section: Introductionmentioning
confidence: 99%
“…A regulatory mechanism has been proposed in which RNAs cross-talk via competing shared miRs (11). In addition, lncRNAs directly interact with RNA-binding proteins and localize to the gene promoter region to regulate gene expression (12). The proposed competitive endogenous RNAs (ceRNAs) mediate the bioavailability of miRs on their targets, thus imposing another level of post-transcriptional regulation (13).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the results demonstrated that CCAT1 may induce EMT to promote cell metastasis in lung adenocarcinoma. lncRNAs have been reported to serve important regulatory roles in the biology of human malignancy (10). Specifically for lung adenocarcinoma, it has already been reported that lncRNAs contribute to the malignant phenotype of tumor cells (11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%